Pengaruh Ukuran Pasir Terhadap Laju Sirkulasi Bed Material Pada Dual Reactor Fluidized Bed - Roziqi, Fahru Ahmad; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya (Teknik Desain Mekanika, 2022)
Abstract DRFB is a type of gasification reactor whose working principle is based on the fluidization process. The fluidization process that occurs in solid objects to behave like a fluid causes the bed material to circulate properly in the gasification reactor and the combustion reactor. Circulation of bed material in the DRFB system requires the help of exhaled fluid. In this study used variations in the size of the sand less than 0.25 mm, 0.25-0.5 mm, 0.5-0.75 mm, and 0.75-1 mm. There are also several controlling variables, such as using silica sand as the bed material, the air velocity of the blower being 9 m/s and the compressor exit air pressure being 25 psi. The results showed that the decrease in size of the bed material affects the increase in the circulation rate of the bed material in the DRFB system. Which for sand size less than 0.25 mm has the highest circulation rate of 14.28 kg/hour. Keywords : Fluidization, Bed Material, Dual Reactor Fluidized Bed